Acculturation preferences of Spaniards towards Middle Eastern and Syrian refugees and their relationship with the stereotypical dimension of morality / Preferencias de aculturación de españoles hacia refugiados sirios y de Oriente Medio y su relación con la dimensión estereotípica de moralidad. Issue 1 (2nd January 2020) - Ordóñez-Carrasco, Jorge L.; Blanc, Andrea; Navas, Marisol; Rojas-Tejada, Antonio J.
ABSTRACT: Acculturation preferences of the majority towards minorities influence how their acculturation process takes place. According to the relative acculturation extended model (RAEM), these preferences depend on the area (public or private) in which it occurs. The aim of this study is to analyse the acculturation preference profiles of Spaniards towards Syrian and Middle Eastern refugees and their relationship with the stereotypical dimension of morality. A total of 400 Spaniards (50% women) responded to a questionnaire indicating their acculturation preferences in the RAEM areas and their perceptions of morality towards this group. Cluster analysis identified three profiles in public areas (assimilation with higher percentage) and four profiles in private areas (integration, exclusion and segregation in similar percentages). Likewise, participants in profiles that imply greater cultural maintenance for refugees (segregation or integration) in private areas perceive a higher degree of morality among refugees (vs. those who do not prefer cultural maintenance: assimilation or exclusion). The results confirm the predictions of the RAEM and the prominent role of morality in acculturation preferences towards refugees in private areas.